Archives : Mirror of Canada Past / Miroir du passé du Canada (Book collections on Project MUSE., 1972)
The Public Archives of Canada mirrors Canada's past, it is a collective national memory, the base of the country's cultural heritage. This volume provides a unique guide to the unusually wide range of items held in the Archives: documents old and new, sketches and diaries, films, recordings, photographs, private letters and government files, maps, plans, treaties, books and paintings -- the stuff of history. The 306 items included in this volume were drawn together as an exhibition to celebrate the centennial of the founding of the Archives. They are organized around thirty-seven themes: each item is fully described and an explanatory note is added where necessary. The 134 photographs, most of them full-page, bring vividly to life the political and cultural heritage of Canada. For all Canadians, and especially for students of Canadian history, this is a valuable source book -- to dip into at lesiure, or as a guide to research resources.